(untitled) (Eurasian Scientific Herald, 2023)
This article discusses specific features of the model for ensuring the harmony of solving physical problems in engineering activities, stages of organization and specific examples of its direct application. Here, the main principles of the modeling process, the formation of the main general professional competencies of the future engineer in the study of fundamental sciences, and the structural and substantive model of the general physics course are presented. Also, the stages of formation of the main general professional competencies of future engineers in the effective application of this model in the educational process are mentioned